Characterization of clays from the Corumbataí formation used as raw material for ceramic industry in the Santa Gertrudes district, São Paulo, Brazil - de Almeida Azzi, Andrezza; Osacký, Marek; Uhlík, Peter; Čaplovičová, Mária; Zanardo, Antenor [UNESP]; Madejová, Jana (Elsevier, 2016)
The Ceramic District of Santa Gertrudes (CDSG) is the largest producer of ceramic floor and wall tiles in Brazil. Tile manufacturers in the CDSG use the single raw material, clayey rocks from the Corumbataí formation. Mineralogical, chemical, thermal and microstructural characterization of the clayey rocks from the Corumbataí formation have been performed in order to better understand effect of the studied properties on dry route tilemaking process. The results revealed different compositional features among the studied clayey raw materials. The bulk samples were dominated by clay minerals associated with quartz, feldspars and minor amount of hematite. All samples were complex mixtures where different types of clay minerals (illite, smectite, illite–smectite, kaolinite–smectite, chlorite, sometimes kaolinite) coexist in variable amount. The amount of clay minerals increased with a higher degree of weathering of studied samples. Different technological behavior was expected for studied raw materials due to their heterogeneous nature, in terms of mineral composition and weathering degree. To improve technological behavior of studied materials during tilemaking process an upgrade of the currently used raw materials preparation is recommended (raw materials maturation, more aggressive milling of raw materials, addition of plastic component and homogeneous mixing of plastic and non-plastic components).
Keywords: Clayey rock; Mineral composition; Technological behavior; Tilemaking; Weathering